2009
DOI: 10.1086/597387
|View full text |Cite
|
Sign up to set email alerts
|

HIV‐1 Tat Protein Suppresses Cholangiocyte Toll‐Like Receptor 4 Expression and Defense againstCryptosporidium parvum

Abstract: Biliary cryptosporidiosis is associated with acquired immunodeficiency syndrome (AIDS) cholangiopathy and occurs almost exclusively in adult patients with AIDS. Infection of biliary epithelial cells (cholangiocytes) with Cryptosporidium parvum induces Toll-like receptor (TLR) 4 expression and stimulates a TLR-dependent response against infection. Here, we tested whether human immunodeficiency virus type 1 (HIV-1) Tat affects TLR expression and, hence, anti–C. parvum defense responses. Using an in vitro model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 45 publications
3
22
1
1
Order By: Relevance
“…It has been reported that the HIV-1 Tat protein increases the half life of the TLR4 mRNA, but decreases TLR4 translation. 43 Recently, it was reported that exposure to the HIV-1 proteins Tat and gp120 significantly alters TLR expression in astrocytes. 44 Together, these results indicate that HIV-1 proteins alter the innate response, supporting our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the HIV-1 Tat protein increases the half life of the TLR4 mRNA, but decreases TLR4 translation. 43 Recently, it was reported that exposure to the HIV-1 proteins Tat and gp120 significantly alters TLR expression in astrocytes. 44 Together, these results indicate that HIV-1 proteins alter the innate response, supporting our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Although bile is thought to be sterile under normal physiological conditions, biliary epithelial cells lining bile ducts (cholangiocytes) are periodically exposed to potentially pathogenic organisms or products derived from these microbes (1)(2)(3)(4). Indeed, cholangiocytes are exposed to bacteria (5-9), viruses (10 -12), and parasites (13)(14)(15)(16). Cholangiocyte pathogen recognition promotes innate and adaptive immune responses (4,(17)(18)(19) through the expression of adhesion molecules (20 -22) and the secretion of cytokines/chemokines (23,24) and antimicrobial peptides (18,23).…”
mentioning
confidence: 99%
“…The two diseases can occur concurrently, with similar opportunistic infections causing each. Bile ducts in AIDS patients appear to be uniquely susceptible to opportunistic infections [11]. Ultrasonogra- "nutritional-like", inflammatory and both of these together [16].…”
Section: Form Non-invasive Inexpensive and Safe Imaging Technique Tmentioning
confidence: 99%